PENINGKATAN PEMBELAJARAN BERWAWANCARA MELALUI METODE LEARNING COMMUNITY SISWA KELAS VIII SMP NEGERI 3 PALLANGGA GOWA - Nur Hafsah Yunus MS (Fakultas Keguruan dan Ilmu Pendidikan Univ. Al Asyariah Mandar Sulbar, 2016)
This study aims to: 1) Planning enhancement of learning converse through the method of learning community eighth grade students of SMP Negeri 3 Pallangga, 2) The increase in learning converse through the method of learning community eighth grade students of SMP Negeri 3 Pallangga, 3) increase learning converse through methods learning community class VIII SMP Negeri 3 Pallangga.Application of community learning methods in the learning process can improve the ability interviewing class VIII SMP Negeri 3 Pallangga Gowa seen from the activities of teachers and students increased. Total percentage in the first cycle of the descriptors were observed as 18:59% who are in the very good category, as much as 37.66%, which is in both categories, as much as 33.49%, which is in the category enough, as much as 7.69%, which is in the category of less, and there are still 2:56 % were in the category is very less and the second cycle are in the very good category, that of the 42 aspects are observed, 35 aspects (83.01%) are in the very good category and 7 facet (16.99%) are in either category. Activities students also saw an increase in cycle I and II, which is about 55.21% in the active category, and 44.79% are in the category of inactive and the second cycle as much as 71.11% in the active category, as much as 26.89% in the inactive category. The results showed in the first cycle there are two students (6:25%) who received grades in the categories of excellent, 6 students (18.75%) scored in both categories, 8 students (25%) scored with enough categories, 12 students (37.5% ) scored with less category, and there are four students (12.5%) gained value by category is very less. There were 15 students (46 875%) which scored in the excellent category, 13 students (40 625%) scored in both categories, 4 students (12.5%) scored with enough categories, and none of the students who are in the category of less and it is less .. it can be concluded that the results of students' ability to converse Class VIII SMP Negeri 3 Pallangga Gowa through community learning methods declared complete because it has met the standard classical completeness, which is above 85% and otherwise managed to show improvement Significant learning.